2009
DOI: 10.1002/ijc.24326
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of prostate cancer in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort

Abstract: The evidence concerning the possible association between physical activity and the risk of prostate cancer is inconsistent and additional data are needed. We examined the association between risk of prostate cancer and physical activity at work and in leisure time in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. In our study, including 127,923 men aged 20-97 years from 8 European countries, 2,458 cases of prostate cancer were identified during 8.5 years of followup. Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
39
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 43 publications
5
39
0
4
Order By: Relevance
“…In accordance with that, Johnsen, et al [14] researched 22 cohort studies. Of these studies, nine showed a reverse association between the risk of prostate cancer and physical aptitude, occupational activity, and leisurely activities.…”
Section: Exercise and The Likely Associations With Prostate Cancersupporting
confidence: 53%
See 1 more Smart Citation
“…In accordance with that, Johnsen, et al [14] researched 22 cohort studies. Of these studies, nine showed a reverse association between the risk of prostate cancer and physical aptitude, occupational activity, and leisurely activities.…”
Section: Exercise and The Likely Associations With Prostate Cancersupporting
confidence: 53%
“…Johnsen, et al [14] describe that certain observational studies were conducted, which provide some initial hints regarding molecular mechanisms with which physical exercise may inhibit prostate cell cancer. It changes the IGF axis increasing the cellular levels of the P53 protein, a DNA regulator which protects the genome through activating the cellular cycle detention, cause DNA to be repaired and/or undergo apoptosis when there are mutations in the genome.…”
Section: The Benefits Of Physical Exercise For Patients In Treatmentmentioning
confidence: 99%
“…We previously reported a significant association between high levels of vigorous activity and reduced risk of advanced PCa in men age 65 years or older, 7 and several recent cohort studies support an association of recreational or occupational activity with reduced risk of advanced and fatal disease. [19][20][21] Patel et al 19 reported a significant 31% reduction in risk of aggressive PCa among men engaged in more than 35 MET-h/wk of activity compared with men reporting no activity, whereas Johnson et al 21 reported no association for leisure time activity but a significant inverse association with advanced disease for manual occupational activity in the European Prospective Investigation Into Cancer and Nutrition (EPIC) cohort. Levels of leisure activity were much higher in EPIC compared with our study, with half of the men having Ն 43 MET-hours of leisure activity per week, reducing the exposure contrast compared with our population.…”
Section: ‫ء‬mentioning
confidence: 99%
“…The conflicting findings may result from alteration of the relationship of progesterone to mammary gland morphogenesis and function that occurs with full-term pregnancy, which may explain the protective effect of early age at first full-term pregnancy (45). In any case, however, breast mitotic activity is in fact highest during the luteal phase of the menstrual cycle, when progesterone levels are also highest.Just as there is considerable support for a role of estrogens in the pathogenesis of breast cancer, there is wide-ranging evidence, including prospective cohort investigations in breast (39), colorectal (38), endometrial (16), lung (58a), ovarian (40), and prostate cancer (26), that increased levels of physical activity are associated with a reduction in cancer risk, including breast cancer risk (33,35,60,65). The hypothesized mechanisms by which exercise reduces breast cancer risk are varied and complex, but evidence is accumulating that aerobic activity results in a negative energy balance (41) and lowers estrogen levels in both pre-and postmenopausal women (5,9,66).…”
mentioning
confidence: 99%
“…Just as there is considerable support for a role of estrogens in the pathogenesis of breast cancer, there is wide-ranging evidence, including prospective cohort investigations in breast (39), colorectal (38), endometrial (16), lung (58a), ovarian (40), and prostate cancer (26), that increased levels of physical activity are associated with a reduction in cancer risk, including breast cancer risk (33,35,60,65). The hypothesized mechanisms by which exercise reduces breast cancer risk are varied and complex, but evidence is accumulating that aerobic activity results in a negative energy balance (41) and lowers estrogen levels in both pre-and postmenopausal women (5,9,66).…”
mentioning
confidence: 99%